The Influece Of Teaching Factory Learning On Student’s Entrepreneurial Interest At Smk Nusatama Padang - Nur Rahmadini; Ezi Anggraini; Asmar Yulastri; Juliana Siregar (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The unemployment rate among vocational high school (SMK) graduates in Indonesi remains high, partly due to low practical skills and entrepreneurial interest. The Teaching Factory learning model is implemented to integrate industrial work environments and procedures into the learning process, enabling students to again real experience in production and marketing. This study aims to. (1) the implementation of teaching factory learning, (2) determine students entrepreneurial interest level, and (3) analyze the effect of teaching factory learning on the entreprenuerial of 12th-garde culinary students at SMK Nusatama Padang. The research employed a quantitative method with a simple linear regression design. The population, which also served as the sampel, consisted of 40 students selected through total sampling. Data were collcted using a Likert-scale questionnaire tested for validity and reliability, complemented by observation and documentation. The result showed that the implementation of teaching factory learning was in the “good” category, and students entrepeneurial interest was high. The regression equation Y = 18,929 + 0,816X, with tcount 7,834 > ttable 2,204 and p = 0,000 < 0,05, indicated a positive and significant effect. The coefficient of determination (R2) of 61,8% revealed that teaching factory learning contributes to variations in students entrepreneurial interest, while the remaining 38,2% is influenced by other factors. In coclusion, direct student involvement in all production processes through teaching factory learning can enhance motivation, self-confidance, and entrepreneurial intention.